Vortex Shedding: A Review on Flat Plate - Teimourian, Amir; Yazdi, Sinag.; Hacisevki, Hasan (Pleiades Publishing Ltd, 2018)
Flat plates, both single and in tandem or side by side arrangement, are widely used in many engineering applications. Despite vast investigations of the flow structures and wakes downstream of these bluff bodies, this unsteady phenomenon yet remains a fundamental issue in many industrial applications. This paper reviews the state of the art concerning the flow over flat plates in different arrangements focusing on plates normal to the flow. Turbulent wake regions are discussed for the flat plates in side by side or tandem arrangement. Numerical studies are reviewed with emphasis on the realized turbulent models. The effect of the chosen turbulence model on the prediction of the wake region is discussed.
Keywords: 2 Circular-Cylinders; Interacting Wakes; Square Cylinders; Flow Structures; Arranged Side; Bluff-Bodies; Tandem; Interference; Forces; 3-Dimensionality